QUALITY EVALUATION OF BIOSIMILAR MEDICINES: AN OVERVIEW - KORKMAZ, Emrah; ÖZDEMİRHAN, Mehmet Emre and YAPAR, Evren ALGIN (Universal Journal of Pharmaceutical Research, 2020)
Biosimilar medicines are biotherapeutics that are similar in quality, safety and efficacy to previously licensed reference biotherapeutics. The slightest change in any stage of production can cause differences in the product. Among the factors, affecting production can be listed as; host cell selection, fermenter type, ambient conditions, broth, substances used for cell culture, fermentation method and purification method. The similarity should be demonstrated by comparative quality, non-clinical and clinical tests. Research and development studies in the biopharmaceutical field bring diversity of quality control methods along with the formulation and manufacturing method of the biosimilars. Although there are some standardized and validated quality control methods given in the internationally recognized pharmacopoeias, there are many in house methods of biopharmaceutical product owners that can only be used as internal quality control methods by them. The main international sources for quality control methods of biopharmaceutics can be given as pharmacopoeias, International Organization for Standardization standards and Organization for Economic Co-operation and Development methods. In this review manufacturing process, regulatory guidelines and quality control of biosimilar medicines briefly are given. Peer Review History: Received 1 February 2020; Revised 13 March; Accepted 28 April; Available online 15 May 2020 Academic Editor: Dr. Asia Selman Abdullah , Al-Razi university, Department of Pharmacy, Yemen, asia_abdullah65@yahoo.com Reviewer(s) detail: Dr. Mohamed Salama , Modern University for Technology & Information, Egypt, salama47@yahoo.com Dr. Maha Khalifa Ahmed Khalifa , Al-Azhar Universit - Cairo, Egypt, mahakhalifa.ahmed@hotmail.com